Anticancer Activity of Carbon Nanotubes-Mediated Hyperthermia Treatment In Murine Breast Cancer Model - Muhammad Redza, Mohd Radzi; Nurliyana, Ahmad Zawawi; Khairunadwa, Jemon (Universiti Teknologi Malaysia, 2019)
Hyperthermia (HT) therapy was introduced as one of the alternatives to treat breast cancer. However, studies have encountered problem with poor specific heat distribution in tumor during HT which lead to the unintentional destruction of normal cells. Therefore, this study explores the integration effect of multiwalled-carbon nanotubes (MWCNT) in combination with hyperthermia for breast cancer therapy. In this study, 5 × 105 EMT6 breast cell was inoculated subcutaneously into right flank of female Balb/c mice. At day 7 post-inoculation, tumor were intratumorally injected with MWCNT and subjected to local HT for 3 consecutive days. The tumor progression was monitored. In another experiment, mice were sacrificed and tumors were harvested for pathological examination and immunohistochemical analysis. Results from this study demonstrated that combined treatment displayed complete tumor eradication and significantly prolonged median survival of mice. Furthermore, histological analysis of tissues from combined treatment showed that the tumor experienced cell necrosis. For HSP70 expression, HT and combined treatment both showed the expression of HSP70 protein corresponding to NIR radiation. In addition, decreased PCNA-positive stained cells was observed in treated group indicated that HT in combination with MWCNT treatment reduced tumor cells proliferation. The results suggested that MWCNT have potential as the anticancer therapeutic effect.